Habitat management decisions for conservation: a conceptual framework - Nichols, James D.; Breininger, David R.; Armstrong, Doug P.; Lacy, Robert C. (Frontiers in Conservation Science, 2024)
The focus of this selecNon of papers is the linkage of habitat and populaNon dynamics for the purpose of conservaNon. We thus provide a general framework for making conservaNon decisions, emphasizing how knowledge of habitat-populaNon linkages fits into this framework. We begin by describing structured decision-making (SDM) as a general approach to making conservaNon decisions. SDM requires development of the following elements: objecNves, acNons, model(s), monitoring and decision algorithm. We then describe adapNve resource management (ARM), a specific type of SDM developed for recurrent decisions characterized by potenNally resolvable uncertainty. Many different classes of acNons can be used to influence animal populaNon dynamics, and modificaNon of habitat is one class of acNon that is frequently used. Habitat management requires models for predicNng responses of the managed system to management acNons, and these models are based on our knowledge of habitat-populaNon linkages. Frequently, these models are decomposed into two submodels, one used to predict habitat changes expected to result from management acNons, and another used to predict populaNon responses to habitat changes. This laeer modeling focuses generally on the influence of habitat change on vital rates governing dynamics of populaNon state variables (variables such as populaNon size or density that describe the status or health of a populaNon). Specific recommendaNons depend on (1) the vital rates and state variable(s) being considered, (2) the relaNve spaNal scales of animal movement and habitat measurement, and (3) the relaNve temporal scales of habitat change and vital rate esNmaNon. Finally, we present an example of an ARM program for habitat management, highlighNng the role of habitat-linked populaNon modeling in this effort.